APPLICATION OF ARTICULATION METHODS WITH EXPERIMENTS TO IMPROVE THE SCIENCE LEARNING OUTCOMES OF 4TH GRADE STUDENTS SD IV NEGERI BANYUPUTIH, KALINYAMATAN, JEPARA REGENCY - Melyani Sari Sitepu; Ana Safitri (Proceeding International Seminar of Islamic Studies, 2021)
This research was motivated by the low science learning outcomes in grade IV SD Negeri 4 Banyuputih, because teachers were less varied in using learning methods. The formulation of the problem is whether the application of the articulation method with experiments can improve science learning outcomes. This study aims to improve student learning outcomes using the articulation method with experiments on science learning. The type of research used was Classroom Action Research. The research subjects were 34 grade IV students. Data collection techniques using test and non-test techniques. The research instruments were test questions and observation sheets. The data analysis techniques used were (1) quantitative data analysis and (2) qualitative analysis. The results showed that there was an increase in the first cycle of students who completed as many as 30 students (88.23%) increased in the second cycle by 33 students (97.05%). ) complete. Teacher's skills in the first cycle were categorized as good, and increased in the second cycle. Student activity in the first cycle of students who completed as many as 28 students (82.35%) increased in the second cycle of students who completed as many as 30 students (88.23%).Keywords: Articulation Method with Experiments, Science Learning Outcomes